(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Perinatal history is often underrated in ophthalmologic consultation and may provide important information in order to establish an assertive diagnosis. Purpose: To report a case of a patient who was evaluated in two hospitals as a child and misdiagnosed with Goltz syndrome. Material and Methods: it was ruled out a syndrome and the existence of three independent diagnoses was proposed: nevus of Ota, non-accommodative esotropia and left facial hemiparesis due to involvement of the VII cranial nerve. Results: A combined left eye strabismus surgery and neodymium Yag laser treatment were performed under sedation over the entire length of the nevus. Conclusion: The presence of facial palsy, strabismus or a nevus directs the physician to interrogate prenatal and perinatal issues to establish a complete diagnosis. The patient received treatment after several years and now she is satisfied.